Perceived Benefits, Knowledge about Cancer and Attitude towards Promotion of Gutkha Amongst Gutkha users from Nepal - Basnet, Bishal Babu; Sharma, Khem Raj (Birat Journal of Health Sciences, 2019)
Introduction: Gutkha, a mixture of areca nut pieces, tobacco and slaked lime, is a potential carcinogen. It causes oral submucous fibrosis. Many people do not possess this knowledge and thus consume gutkha daily. The consumption is highly prevalent in Nepal because of easy availability of this material. Although ban of advertisement is implemented in Nepal in electronic media, the impact has not been significant. Objective: To find the prevalence of different beneficial effects cited, to determine awareness about cancer and attitude towards ban of advertisement, production and sale in current gutkha users from rural Terai dwellers of Nepal. Methodology: We interviewed 1217 households in a community survey in which 151 were current gutkha consumers, their responses about perceived benefits, cancer knowledge and views on ban of its sale and promotion was analyzed. The relationship with demographic variables were tested with Chi-square test with level of significance set at 0.05. Results: Among the current users, the reason of consuming gutkha was mostly ’feeling of well-being’ (38.4%), about 40% thought it can cause cancer. The knowledge was not associated with gender, age group and literacy but statistically related with marital status (p<0.05). Majority were in favor of ban on advertisement (74.2%) and on production, sale and consumption (70.2%). Conclusion: The level of knowledge of cancer causation is very low and education level had not been significantly associated to knowledge. More gutkha users were in favor of its ban which is a positive finding.